This preview shows page 1. Sign up to view the full content.
Unformatted text preview: nb=n+1; Aug=[A b]; %forward elimination for k=1:n-1 for i=k+1:n factor=Aug(i,k)/Aug(k,k); Aug(i,k:nb)=Aug(i,k:nb)-factor*Aug(k,k:nb); end end %back substitution x=zeros(n,1); x(n)=Aug(n,nb)/Aug(n,n); for i=n-1:-1:1 x(i)=(Aug(i,nb)-Aug(i,i+1:n)*x(i+1:n))/Aug(i,i); end...
View Full Document
This note was uploaded on 09/27/2011 for the course EGM 3344 taught by Professor Raphaelhaftka during the Spring '09 term at University of Florida.
- Spring '09